2019
DOI: 10.1063/1.5091070
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic determination of interconversion rates among three nuclear spin isomers of methane in crystalline II

Abstract: We measured infrared absorption spectra of crystalline II of CH4 and succeeded in detecting a prominent Q(2) peak in the ν3 vibrational region by rapid cooling after annealing as well as previously reported rovibrational and librational-vibrational peaks. The integral intensities of the R(0), R(1), and Q(2) peaks were found to show biexponential dependence on time. This clearly demonstrates the interconversion among the three nuclear-spin isomers occupying low-lying rotational levels. The two relaxation rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Recently, Sugimoto et al 13 suggested that the use of eq 1 to fit the change of the peak area vs time might not be entirely applicable for a system of more than two spin isomers. Using a much faster cooling from 30 to 5 K to prepare their samples than they used in previous work, they found that their data in the 5−7 K range can be fit using…”
Section: ■ Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Sugimoto et al 13 suggested that the use of eq 1 to fit the change of the peak area vs time might not be entirely applicable for a system of more than two spin isomers. Using a much faster cooling from 30 to 5 K to prepare their samples than they used in previous work, they found that their data in the 5−7 K range can be fit using…”
Section: ■ Results and Analysismentioning
confidence: 99%
“…Recently, Sugimoto et al suggested that the use of eq to fit the change of the peak area vs time might not be entirely applicable for a system of more than two spin isomers. Using a much faster cooling from 30 to 5 K to prepare their samples than they used in previous work, they found that their data in the 5–7 K range can be fit using We found that biexponential fitting is only necessary for isotherms of R (1) peak deposited at 30 K but not for R (0), since the fit with one exponential is excellent (see Figure ).…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations